CORRUPTION IN MATCH-FIXING WITHIN SPORTS: THE NEED TO REGULATE FUTURE LEGISLATION (A COMPARATIVE STUDY AND LESSON FROM THE AUSTRALIAN SYSTEM OF LAW) - Silalahi, Ranto Sabungan (UI Scholars Hub, 2020)
The Indonesian football league has been devastated greatly because of match-fixing, a problem that has caused the decline of the country’s achievements in international events. The ongoing mechanism of using sports law or lex sportiva is considered ineffective because it provides no deterrent effect on offenders. The country may learn from Australia, who has gained many international sports achievements by previously eradicating match-fixing in sports, including football. Australia has included match-fixing among acts of sports corruption, and offenders may be sanctioned both by receiving criminal punishment from a law authority and disciplinary sanction from a sport or football authority. To prevent and address the involvement of gambling syndicates in many instances of match-fixing in football matches, the country has enacted a national policy on the codes of conduct and anti-match-fixing measures in sports and established a special unit to coordinate the law authority and sports authority. Although it has a different system of law, Indonesia may learn from Australia in eradicating match-fixing in football and may have many great achievements in international events as a result.